Upgrading biomass to high-added value chemicals: synthesis of monoterpenes-based compounds using catalytic green chemical pathways (2025)
Monoterpenes derived from various biomass constitute an important platform for synthesizing fragrances, intermediates, and pharmaceuticals. In this review, the most recent and relevant transformations of terpenes are discussed with the primary focus on heterogeneous catalysis emphasizing green chemistry and green chemical engineering aspects. This review aims to outline significant recent advancements in the transformations of terpenes of particular importance for academic and industrial research. This is accomplished by highlighting the most pivotal reactions, including oxidation, epoxidation, hydroformylation, CO2 cycloaddition, isomerization, condensation, and one-pot synthesis (such as tandem and telescopic reactions), using heterogeneous catalytic routes that have been published in the literature in the last decade. The review provides insights on the catalyst design for the transformations mentioned above tailoring selectivity and highlights the structure–activity relationship